Diastereoselective Syntheses of Highly Substituted Methylenecyclopropanes via Copper- or Iron-Catalyzed Reactions of 1,2-Disubstituted 3-(Hydroxymethyl)cyclopropenes with Grignard Reagents - Xie, Xiaocong; Fox, Joseph M. (Synthesis, 2013)
Described are diastereoselective syntheses of highly substituted methylenecyclopropanes from 1,2-disubstituted 3-(hydroxymethyl)cyclopropenes with allylic ether leaving groups, compounds that were constructed via alkylation of cyclopropenecarboxylic acid dianions. Substitution reactions of 1,2-disubstituted 3-(hydroxymethyl)cyclopropenes with Grignard reagents proceed with good yield and high diastereoselectivity. Under copper(I)-catalyzed conditions, the substitution reactions proceed to give syn-addition products, whereas Fe(acac)3 catalysis gives the products of anti-addition.
Keywords: cyclopropene; diastereoselective; dianion; methylenecyclopropane; substitution